2020
DOI: 10.14712/18059694.2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Acute Compartment Syndrome

Abstract: Acute compartment syndrome occurs most frequently in connection with injuries, terminal or chemical damage of tissues, ischemia, the activity of toxins or in patients with tissue ischemia or muscle necrosis. Clinical findings have found pronounced pain, followed by paresthesias, pallor, and paresis. Decreased pulsation of arteries has also been a frequent finding. In severe forms decompressive fasciotomy has been indicated within the first 12–24 hours after diagnosis. In the following paper, the authors presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…There are also cases of non-traumatic compartment syndrome, which may be seen in the setting of bleeding disorders, anticoagulation use, nephrotic syndrome, toxic envenomation, massive fluid resuscitation, revascularization procedures, and muscle infection. 4 As demonstrated by Hope et al, cases of compartment syndrome not associated with acute fracture often go undiagnosed and there is a risk of delayed treatment with more devastating sequela and functional loss. 5 Specifically, Hope et al reported that patients without the presence of fracture were more likely to have muscle necrosis at the time of fasciotomy than patients with ACS in the setting of acute fracture.…”
Section: Discussionmentioning
confidence: 99%
“…There are also cases of non-traumatic compartment syndrome, which may be seen in the setting of bleeding disorders, anticoagulation use, nephrotic syndrome, toxic envenomation, massive fluid resuscitation, revascularization procedures, and muscle infection. 4 As demonstrated by Hope et al, cases of compartment syndrome not associated with acute fracture often go undiagnosed and there is a risk of delayed treatment with more devastating sequela and functional loss. 5 Specifically, Hope et al reported that patients without the presence of fracture were more likely to have muscle necrosis at the time of fasciotomy than patients with ACS in the setting of acute fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Both soft tissue and vascular injuries are unusual but essential causes of OCS. 3 Only few cases have been reported after highenergy road traffic accidents; OCS also occurs after a relatively minor trauma. 3 The etiology of OCS can also be iatrogenic, Transradial angiography and intervention can result in compartment syndrome.…”
Section: Western Medicine Etiologymentioning
confidence: 99%
“…3 Only few cases have been reported after highenergy road traffic accidents; OCS also occurs after a relatively minor trauma. 3 The etiology of OCS can also be iatrogenic, Transradial angiography and intervention can result in compartment syndrome. 10 The incidence of OCS was 1.3% in China during radial artery intervention, which needed to be dealt with emergently.…”
Section: Western Medicine Etiologymentioning
confidence: 99%
See 2 more Smart Citations